Vector mechanics for engineers : - Beer, Ferdinand Pierre (McGraw-Hill/Higher Education, 2007)
The eighth edition Vector mechanics for engineers retains the unified presentation of the principles of kinetics which characterized the previous seven editions. The concepts of linear and angular momentum are introduced in chap.12,....